2002
DOI: 10.3168/jds.s0022-0302(02)74129-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Lactic Acid Starter and Probiotic Bacteria Used for Fermented Dairy Products

Abstract: Interactions among lactic acid starter and probiotic bacteria were investigated to establish adequate combinations of strains to manufacture probiotic dairy products. For this aim, a total of 48 strains of Streptococcus thermophilus, Lactobacillus delbrueckii subsp. bulgaricus, Lactococcus lactis, Lactobacillus acidophilus, Lactobacillus casei, and Bifidobacterium spp. (eight of each) were used. The detection of bacterial interactions was carried out using the well-diffusion agar assay, and the interactions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
1
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(146 citation statements)
references
References 17 publications
4
125
1
16
Order By: Relevance
“…3b). Vinderola et al (2002) proved that the viability of starter bacteria and probiotics can be inversely related to the salt concentration. Lower levels of salt in moisture for the initial storage times can be thus associated with higher microbial growth (Kasimoglu et al 2004).…”
Section: Survival Rate Of the Probioticmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). Vinderola et al (2002) proved that the viability of starter bacteria and probiotics can be inversely related to the salt concentration. Lower levels of salt in moisture for the initial storage times can be thus associated with higher microbial growth (Kasimoglu et al 2004).…”
Section: Survival Rate Of the Probioticmentioning
confidence: 99%
“…During the ripening process, low amounts of salt used diffuse into the cheese structure so that difference in the salt content at the center and periphery decreases with increasing storage time. This fact contributes not only to the flavor of the cheeses but also has an impact on the growth and activity of starter and probiotic microorganisms (Vinderola et al 2002). On the other hand, Bora et al (2009) revealed that aqueous suspension of B. coagulans spores in buffer solutions of pH 1.2 to 8.0 had rapid degradation with maximal stability in pH 6.8.…”
Section: Survival Rate Of the Probioticmentioning
confidence: 99%
“…merupakan BAL yang dilaporkan memiliki ketahanan yang lebih baik dalam saluran pencernaan manusia (Gomez & Malcata 1999). Oleh karena itu penelitian mengenai penambahan kedua bakteri ini pada kultur campuran menjadi salah satu topik yang menarik karena adanya interaksi antara bakteribakteri tersebut dengan bakteri kultur starter (Vinderola et al 2002) yang dapat mempengaruhi kualitas produk yang diinginkan (Gardini et al 1999).…”
Section: Kualitas Yoghurt Yang Dibuat Dengan Kultur Dua (Lactobacilluunclassified
“…Vinderola et al (2002) Kadar protein sampel yoghurt pada penelitian ini relatif tidak terlalu berbeda antara sampel yang satu dengan yang lain dan berada pada rentang 0,23-0,30% (b/v). Nilai kadar protein pada yoghurt yang dibuat dengan dua kultur bakteri memiliki nilai yang relatif lebih rendah, yaitu pada rentang 0,23-0,26% (b/v), sedangkan yoghurt yang dibuat dengan kultur tiga bakteri berada pada rentang 0,27-0,30% (b/v).…”
Section: Kadar Asam Laktatunclassified
“…Susu fermentasi didefinisikan sebagai produk susu yang melibatkan mikroorganisme untuk menghasilkan flavour, warna, tekstur dan konsistensi yang diinginkan dan mampu mencegah lactose intolerance (Vinderola et al, 2002 (Kanbe, 1992).…”
unclassified